The value of brain magnetic resonance imaging in the early diagnosis of neuropsychiatric systemic lupus erythematosus - Lai, J M (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2016)
OBJECTIVE: To investigate the value of brain magnetic resonance imaging (MRI) in evaluating the intracranial injuries in patients with juvenile onset systemic lupus erythematosus (SLE)